The Scholems : a story of the German-Jewish bourgeoisie from emancipation to destruction - Geller, Jay Howard (2019)
Zusammenfassung: "A collective biography of the family of the Jewish scholar Gershom Scholem and a social history of the Jewish middle class in Germany from the era of emancipation through the Holocaust"–(Provided by publisher.)